1957
DOI: 10.1017/s0022029900008839
|View full text |Cite
|
Sign up to set email alerts
|

678. The effect of variations in nutrient intake upon the yield and composition of milk II. Factors affecting rate of eating roughage and responses to an increase in the amount of concentrates fed

Abstract: With 5 Figures)The practical application of the results of closely controlled experiments on the effects of different levels of concentrate intake may be affected by the lack of control of roughage intakes of individual cows which occurs in most dairy herds. Individual cows show considerable variation in their ability to ingest and utilize roughage (1,2,3), which, together with the effects of competition, can give rise to considerable differences in individual plane of nutrition when roughages are rationed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
10
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 10 publications
8
10
0
Order By: Relevance
“…The increase in the rate of intake as goats get older is in agreement with previous trials on cows: primiparous cows ate more slowly than multiparous ones (Burt, 1957;Beauchemin and Rode, 1994;Neave et al, 2017). Moreover, lactating animals tend to eat more than dry ones as their requirements are higher (Campling and Morgan, 1981).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The increase in the rate of intake as goats get older is in agreement with previous trials on cows: primiparous cows ate more slowly than multiparous ones (Burt, 1957;Beauchemin and Rode, 1994;Neave et al, 2017). Moreover, lactating animals tend to eat more than dry ones as their requirements are higher (Campling and Morgan, 1981).…”
Section: Discussionsupporting
confidence: 89%
“…As observed since a long time in cows, there is a high variation among individuals in feed intake pattern (Burt, 1957). The present study has clearly shown that there was a rather good repeatability for a given goat of its feed intake pattern across 2 years.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…However, the initial milk yields and the range of yields of these experiments were relatively low. Given a wide range in milk yields, current yield rather than stage of lactation may be the major determinant of production response (Burt 1957). In the current experiments, production responses similar to those reported in early lactation of at least 1 kg milk/kg supplement were achieved in mid-late lactation, with cows producing greater than 18 kg milk/cow.day.…”
Section: Significant Effects Of Level Of Grain Intake (Kg Dm/cowdamentioning
confidence: 99%
“…Reviews by Blaxter (1956b), Burt (1957a), J awe tz (1956) and Reid (1956) summarize the early experimental work in dairy rations wherein different planes of nutrition (energy) were fed. They report both long-and short-term experiments in which feeding at an increased plane of nutrition has resulted in higher levels of FCM production, but with a diminished re sponse for each additional increment of energy.…”
mentioning
confidence: 99%